2021
DOI: 10.1021/acs.nanolett.1c03483
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CO2 Electrochemical Reduction Performance over Cu@AuCu Catalysts at High Noble Metal Utilization Efficiency

Abstract: The electrochemical CO 2 reduction reaction (CO 2 RR) represents a viable alternative to help close the anthropogenic carbon cycle and convert intermittent electricity from renewable energy sources to chemical energy in the form of value-added chemicals. The development of economic catalysts possessing high faradaic efficiency (FE) and mass activity (MA) toward CO 2 RR is critical in accelerating CO 2 utilization technology. Herein, an elaborate Au−Cu catalyst where an alloyed AuCu shell caps on a Cu core (Cu@… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…= 1.2) than Ru–Ru scattering (C.N. = 4.4) demonstrates the Ru atoms still form small clusters instead of dissolving in Ni matrix 33 . This evidence indicates Ru and Ni species are in separated phases with strong interactions rather than a solid-solution alloy 34 .…”
Section: Resultsmentioning
confidence: 94%
“…= 1.2) than Ru–Ru scattering (C.N. = 4.4) demonstrates the Ru atoms still form small clusters instead of dissolving in Ni matrix 33 . This evidence indicates Ru and Ni species are in separated phases with strong interactions rather than a solid-solution alloy 34 .…”
Section: Resultsmentioning
confidence: 94%
“…Electrocatalysts, such as Au, Ag, Cu, etc., are well known as popular choices for experimental designs due to their CO 2 reduction activity, [3–27] although, these metals require high overpotentials. The overpotentials of ${\ge }$ 0.3 V, ${\ge }$ 0.6 V, and ${\ge }$ 0.9 V are required for Au, Ag, and Cu electrocatalysts, respectively [28] .…”
Section: Introductionmentioning
confidence: 99%
“…In the electroreduction of CO 2 , Cu exhibits special properties, and it is the only metal that can electrically reduce CO 2 to C 2+ products currently. However, as experimental studies have shown that CO 2 ER on Cu will generate H 2 and various C 1 , C 2 , and C 3 products, the product selectivity of Cu catalysts is still an urgent problem to be solved. Accordingly, many modulation strategies have been applied in Cu-based catalysts to improve their electrocatalytic performance. A typical one is a bimetallic strategy, and there have been quite a few experimental results to prove the effectiveness of this scheme, such as Zn, Ag, , and Au, whose introduction into Cu will enhance the selectivity of C 2 oxygenates in the CO 2 ER. Among them, the CuAu alloy that changes the C 1 /C 2 product ratio with the change of the element composition ratio has attracted our attention. The pioneering report of CuAu alloy for CO 2 ER comes from Jia and co-workers, and their report demonstrated that Cu 36.9 Au 36.1 /NCF shows high Faraday efficiency (∼28%) for the production of C 2 H 5 OH.…”
mentioning
confidence: 99%